Features and algorithm of treatment of bacterial vaginitis - Yuldasheva, Farangiz Ismatiloevna (Science and Education, 2023)
Infectious and inflammatory diseases of the female genital organs caused by various sexually transmitted pathogens or non-specific microflora represent a serious medical and social problem in obstetrics and gynecology. Bacterial vaginosis (other names: vaginal dysbiosis (dysbiosis)) - this is an infectious non-inflammatory syndrome characterized by a sharp decrease or absence of lactoflora and its replacement by polymicrobial associations of anaerobes and gardnerella, the concentration of which reaches 109-1011 degrees RFO/ml of vaginal discharge.